Effect of molybdenum induced hypocuprosis on copper and molybdenum levels of plasma, hair and liver in buffalo calves - SINGH, C; RANDHAWA, S S; SINGH, SWARAN (The Indian Journal of Animal Sciences, 2016)
The objective of this study was to determine the clinical effects, changes in concentrations of Cu and Mo in plasma, hair, liver and red cell parameters of buffalo calves fed on high Mo diet. Male buffalo calves (12), 1–1.5 year-old were assigned to either control (4) or deficient group (8) on the basis of their body weight. Control group was regularly supplemented with 30 mg of elemental copper and calves of deficient group were fed fresh green fodder sprayed with 0.04% sodium molybdate solution to provide 30 ppm of molybdenum for 180 days. Samples of blood, hair, and liver tissue were collected at regular intervals. Hemoglobin and PCV were determined in whole blood. Concentrations of copper and molybdenum were measured in plasma, hair and liver tissue. Fodder samples were analysed for proximate principles, cell wall constituents, Ca, P, Mg, Cu, Mo and Zn. Salient clinical signs were intermittent diarrhea, varying degree of skin and hair depigmentation. Bilateral swelling of hock joints and transitory lameness occured in one calf each. Daily weight gain was lower in molybdenum fed calves as compared to control however, the weight loss occurred only during 45–135 days. Plasma copper was unaffected. Copper concentration of hair and liver declined in 180 days. There was no change in plasma molybdenum concentration. Hair molybdenum content increased after 180 days of molybdenum feeding. Liver molybdenum concentration was significantly high throughout the experiment as compared to control group. Haemoglobin and PCV were not affected by excess molybdenum feeding. Hair copper concentration of 6 ppm or below may be taken as indicator of molybdenum induced copper deficiency in buffaloes.